Mechanisms of impact and experiences of a person-centred transition programme for adolescents with CHD: the Stepstones project - Markus Saarijärvi; Lars Wallin; Philip Moons; Hanna Gyllensten; Ewa-Lena Bratt (BMC, 2021)
Abstract Background During the past decade there has been some evaluation of transition programmes for adolescents with chronic conditions. However, this has rarely involved process evaluations focusing on mechanisms leading to outcomes, thus hampering implementation of these complex interventions. Our aim was to (I) describe adolescents' and parents' experiences of participating in a person-centred transition programme aiming to empower them in transition to adulthood and (II) explore the mechanisms of impact. Methods A qualitative process evaluation was performed, embedded in a randomized controlled trial evaluating the effectiveness of a transition programme for adolescents with congenital heart disease in Sweden. A purposive sample of 14 adolescents and 12 parents randomized to the intervention group were interviewed after participation in the programme. Data were analysed deductively and inductively in NVivo v12. Results Experiences of participation in the transition programme were generally positive. Meeting a transition coordinator trained in person-centred care and adolescent health and embarking on an educational process based on the adolescents' prerequisites in combination with peer support were considered key change mechanisms. However, support to parents were not sufficient for some participants, resulting in ambivalence about changing roles and the unmet needs of parents who required additional support. Conclusions Participants experienced increased empowerment in several dimensions of this construct, thus demonstrating that the transition programme was largely implemented as intended and the evidence-based behaviour-change techniques used proved effective in reaching the outcome. These findings can inform future implementation of transition programmes and illuminate challenges associated with delivering a complex intervention for adolescents with chronic conditions.